Opportunities and Obstacles in the Prevention of Skin and Soft-Tissue Infections Among Military Personnel. (28th November 2019) - Millar, Eugene V; Schlett, Carey D; Law, Natasha N; Whitman, Timothy J; Ellis, Michael W; Tribble, David R; Bennett, Jason W
Abstract: Introduction: Skin and soft-tissue infections (SSTIs) are an important cause of infectious disease morbidity among military populations. Due to the high direct and indirect costs associated with SSTIs, particularly with methicillin-resistant Staphylococcus aureus (MRSA) infections, there remains a critical need for the development and evaluation of SSTI prevention strategies among high-risk military personnel. Herein, we review efforts of the Infectious Disease Clinical Research Program (IDCRP) related to the prevention of SSTIs in the military. Methods: The IDCRP of the Uniformed Services University has conducted clinical research protocols on SSTI epidemiology and prevention among military personnel since 2009. Observational studies have examined the epidemiology of Staphylococcus aureus colonization and SSTI in training and deployment settings. Two randomized controlled trials of personal hygiene strategies for SSTI prevention at Marine Corps Base Quantico (Virginia) and Fort Benning (Georgia) were performed. Lastly, two vaccine trials have been conducted by the IDCRP, including a Phase 2 S. aureus vaccine trial (currently ongoing) among military trainees. Results: Military recruits and deployed personnel experience an intense and prolonged exposure to S. aureus, the major causative agent of SSTI. The burden of S. aureus colonization and SSTI is particularly high in military trainees. Hygiene-based trials for S. aureus decolonization among military trainees were not effective in reducing rates of SSTI. In January 2018, the IDCRP initiated a Phase 2 S. aureus vaccine trial among the US Army Infantry training population at Fort Benning. Conclusions: In the military, a disproportionate burden of SSTIs is borne by the recruit population. Strategies relying upon routine application of agents for S. aureus decolonization have not been effective in preventing SSTIs. A novel S. aureus vaccine candidate is being currently evaluated in a military training population and may represent a new opportunity to prevent SSTIs for the military.